Growth of pedagogical content knowledge and 'understanding mathematics in depth': conceptions of pre-service teachers. Issue 2 (14th March 2020) - Stevenson, Mary
ABSTRACT: It is generally agreed that good subject knowledge is an important prerequisite for successful teaching. However, what constitutes good subject knowledge is debated, with multiple perspectives taken by policymakers, researchers and schools. This article reports on research into interpretations of 'understanding mathematics in depth' (UMID) of pre-service secondary mathematics teachers at an English university, some of whom had completed a Subject Knowledge Enhancement course prior to their teacher training programme. Qualitative data were drawn from semi-structured interviews with the teachers, and an in-depth case study of one of the sample. Analysis of data revealed that knowledge growth was located mostly within pedagogical content knowledge. UMID was articulated as 'knowing why' and 'being able to communicate'. Additionally, non-elicited themes emerged, relating to the way in which teachers' knowledge develops. Findings highlight relevant messages for policy and practice regarding the integration of subject matter knowledge and pedagogical content knowledge.